The invasion of Undaria pinnatifida to a Macrocystis pyrifera kelp in Patagonia (Argentina, Southwest Atlantic) - Raffo, María Paula (2009)
Biological invasions can alter the biodiversity of native communities generating an ecological impact that in many cases is irreversible. In 2001, Undaria pinnatifida invaded Macrocystis pyrifera kelp in Cracker Bay (42°56′S, 64°27′W; Northern Patagonia, Argentina). The possible impact of that invasion was evaluated in March 2004 with a study of population and morphological parameters of both kelp species and their associated holdfast biodiversity. Three nearby areas of spatial distribution of the kelps were differentiated, one dominated by M. pyrifera (M), an intermediate area characterized by M. pyrifera and U. pinnatifida (M+U), and another dominated by U. pinnatifida (U). In each area, sporophytes in nine quadrats of 1 m2 were collected. The density and biomass m−2, the height of the sporophytes and the size of the holdfast of M. pyrifera did not diminish in the presence of U. pinnatifida. The richness, abundance and diversity of the flora associated with the holdfast of both kelps were similar, whereas these parameters were higher in the case of the fauna associated to M. pyrifera than U. pinnatifida Results obtained in this work suggest that, at this invasion stage, there is no evidence of interspecific competition. Nevertheless, since density and diversity of the fauna associated with the holdfast is different, we expect community changes if the U. pinnatifida invasion continues to expand.